PSYCHOLOGICAL AND PEDAGOGICAL CHARACTERISTICS OF STUDENTS IN THE PROCESS OF DEVELOPING INDEPENDENCE - Isakhanova Mohidil Erkinovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article deals with the pedagogical and psychological aspects of the development of independence among schoolchildren through the performance of independent work. Based on the views of scientists, the psychological possibilities and effectiveness of the organization of independent work are consecrated.